Ensuring Equal Opportunities in an English-for-Specific-Purposes Course for Working-While-Studying Technical Students - Irina Sergeevna Oblova; Irina Gennadyevna Gerasimova (MDPI AG, 2024)
The number of technical students combining work and studies has increased recently. More and more students decide to gain professional experience as early as possible, resulting in a lower attendance rate. This is highly relevant to master's degree students who struggle to succeed in both academic and professional activities, necessitating research into academic attainment strategies. The paper describes the types of working students, their needs in English, and proposes a way to improve their academic achievement, including English proficiency. A series of tests and an interview were administered to a sample of 363 master's degree students learning technical English. The chi-square test, Fisher's test and the Mann-Whitney Z-test were employed in order to assess the language skills acquired by students in blended learning and offline classes, and to validate the designed blended ESP course featuring an e-course and classroom lessons. The findings of the research indicated that working-while-studying students enrolled in the blended course made more significant progress in their English skills, particularly in reading and writing, compared to non-working students who had only traditional offline lessons. The results provide insights concerning the benefits of blended learning to ensure equal opportunities for working-while-studying students and their ways of adapting to a changing learning environment.